Assessing the Effect of Covid -19 Pandemic to Resource Sharing Through Interlibrary Loan Services of Qatar National Library - Rowena O. Aquino (15791821) (2023)
This poster was given by Rowena O. Aquino, Qatar National Library As public facilities such as libraries close down due to the Covid-19 pandemic, academic resources and print collections have become inaccessible for acquiring information. The poster aims to address the impact and changes in the library services and document supply, particularly in Interlending and Document Supply Services offered by the Qatar National Library amidst the Covid-19 Pandemic. This type of service allows open access to library resources and connection with peer libraries to share resources and knowledge to various stakeholders. This poster provides insights on how information is accessed by patrons through this service along with the challenges and alternatives during the pandemic.